Motherhood in Jane Austen’s Pride and Prejudice & Prima Santika’s Three Weddings and Jane Austen - Fauziyyah, Hafizhah; Pramesti, Tri (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study explores the feminist perspective on motherhood in Jane Austen's Pride and Prejudice and Prima Santika's Three Weddings and Jane Austen, concentrating on the influence of mother figures on their daughters' romantic and wedding options. The central issue is how different mother approaches reflect broader societal expectations and individual freedom. The research uses a qualitative analysis method, directed by feminist theory and the attachment theory of John Bowlby and Mary Ainsworth, alongside the comparative literature theory by Wellek and Warren. The findings show that Mrs. Bennet's obsession with securing beneficial marriages for her daughters mirrors early 19th-century English societal norms, where wedding was crucial for financial security and social status. In contrast, Bu Sri's modern approach stresses individual autonomy and emotional well-being, balancing traditional values with individual preference. This study indicates that promoting individual autonomy, providing dynamic support, and balancing traditions with modern parenting can encourage healthier family dynamics.